A Comparison of Spiritual Therapy and Relaxation on Anxiety Levels in Preoperative Patients: A Scoping Review - Ika Dwi Purwaningsih; Titih Huriah (Indonesian Journal of Global Health Research, 2026)
Surgical procedures can cause stress and anxiety in most preoperative patients. Spiritual therapy and relaxation therapy can be alternative therapy to reduce preoperative anxiety. This study aims to critically analyze and compare scientific evidence regarding the effectiveness of spiritual therapy and relaxation on preoperative patient anxiety levels. The method used in this study was a scoping review of research articles with a randomized controlled trial (RCT) design. Article quality assessment was carried out using the Critical Appraisal Skills Program (CASP) instrument. The reviewed articles focus on spiritual therapy interventions (prayer, hypnosis, healing touch) and relaxation in preoperative patients. Based on the results obtained, it was found that most articles showed that spiritual therapy and relaxation were effective in significantly reducing preoperative anxiety levels. Therefore, it can be concluded that spiritual therapy and relaxation are proven effective in reducing preoperative patient anxiety. This integration can be recommended to improve the quality of care and patient safety.